Prevalence and associated factors of meconium aspiration syndrome among neonates admitted to Neonatal Intensive Care Units in Public Hospitals of Harari Region, Eastern Ethiopia - Jabir Aman; Bikila Balis; Naol Oda; Dawit Tamiru; Tadesse Gure Eticha; Dawit Firdisa; Aboma Motuma (PLoS ONE, 2026)
Background Meconium aspiration syndrome is a life-threatening respiratory disease affecting around 5% of neonates worldwide. Although several studies have been conducted in developed countries, data on meconium aspiration syndrome and its associated factors remain limited in low-resource settings, including Ethiopia. Therefore, this study aimed to determine the meconium aspiration syndrome and associated factors among neonates admitted to the neonatal intensive care unit at public hospitals in Harari region, Eastern Ethiopia. Method A retrospective hospital-based cross-sectional study design was conducted among all neonates admitted from January 1 to December 30, 2023 and data were extracted from patient charts during April 1–30, 2025. A simple random sampling technique was employed to select 417 charts of neonates admitted to the neonatal intensive care unit. The data were collected by a data extraction checklist via Kobo Toolbox. Descriptive statistics and binary logistic regression were used in SPSS version 25 (IBM Corp., Armonk, NY, USA) for the analysis. Adjusted odds ratios with 95% confidence intervals were used to declare statistical significance at a p-value ≤ 0.05. Results The prevalence of meconium aspiration syndrome among neonates admitted to the neonatal intensive care unit was 24.2% [95% CI, 20.2–28.6]. Factors significantly associated with meconium aspiration syndrome were post-term gestation [AOR = 9.05, 95% CI 2.38–34.41], antepartum hemorrhage [AOR = 3.34, 95% CI 1.31–8.60], prolonged labor [AOR = 3.06, 95% CI 1.27–7.36], premature rupture of membranes [AOR = 3.65, 95% CI 1.28–10.45], low Apgar scores at 5th minute [AOR = 11.27, 95% CI 3.44–36.92] and intrapartum thick meconium passage [AOR = 5.98, 95% CI 2.6–13.6]. Conclusions and recommendations These findings indicate a high prevalence of meconium aspiration syndrome, and to reduce its impact, targeted clinical interventions should be implemented. Pregnancies reaching 42 weeks of gestation, prolonged labor, and high-risk conditions such as antepartum hemorrhage, premature rupture of membranes, or the presence of thick meconium are important factors to consider. Careful monitoring and appropriate management may be warranted in these cases.